Islamic Value-Based Learning Strategies to Foster Students' Faith and Noble Character - Achmad Ismail (International Journal of Islamic Education Studies, 2025)
Low internalization of Islamic values among secondary school students presents a challenge for educators seeking to develop both faith (iman) and noble character (akhlaq). This study aims to identify effective teaching strategies that foster spiritual and moral development through a Systematic Literature Review (SLR). The review systematically analyzed peer-reviewed studies published within the last ten years, focusing on instructional strategies, motivational techniques, and relational practices in Islamic value-based education. Data were collected from multiple databases, including Scopus, Web of Science, and Google Scholar, and analyzed thematically to identify patterns, best practices, and implementation challenges. The findings reveal that effective strategies include contextualized instruction, collaborative and project-based learning, reflective activities, and technology integration, which enhance students’ understanding of Islamic principles and promote ethical behavior, empathy, and moral reasoning. Positive teacher-student relationships, characterized by trust, empathy, and ethical modeling, further strengthen motivation and value internalization. Challenges such as diverse student backgrounds, limited resources, curriculum constraints, and cultural sensitivities were also identified, yet holistic approaches combining instructional, motivational, and relational practices effectively foster iman and akhlaq. This study provides evidence-based recommendations for educators and policymakers to implement value-based learning strategies that cultivate both spiritual and ethical development, preparing students to embody Islamic values in their daily lives.